Pet Care Management System - Yeow, Jing Ru; Kamaludin, Hazalila (Applied Information Technology And Computer Science, 2023)
The web-based Pet Care Management System is developed for Pet’s Village, which currently uses a manual system to handle all customer reservations. The manual system results in wasting time and energy, data loss, and the possibility of an error occurring. Hence, the system aims to systematically process reservations and use the database for data storage. The prototype model is used in the development of the system. Besides that, the main language used in the developing process is HTML, CSS, and PHP. The system is used to automate the current reservation management process in Pet’s Village by computerizing the manual system. Also, it should be able to implement a paperless environment concept in the filing system. Based on the testing result, all the module is passed from the test plan list, and this system is accepted by the user based on the user acceptance testing.